PHASE COMPOSITION AND CRYSTAL STRUCTURE OF DURIAN (DURIO ZIBETHINUS) HUSK WASTE POWDER USING RIETVELD METHOD - Khairiah Khairiah; Lia Afriyanti Nasution (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2018)
Based on previous research on electrical analysis of electrolyt pastes from durian husk waste as biobatteries that generate an electric voltage about 1.5 volts. Researchers want to develop durian husk waste material to commercial that was increasing the electrical voltage with nanotechnology. It was  known that when the particle size went to the nanometer scale, this phenomenon affects some material properties, one of which was the increase in electrical conductivity. The nanomaterial derived from durian husk waste as a biobattery was synthesized by coprecipitation method which was one of development methods of nanotechnology. Based on the analysis of SEMand XRD characterization data of durian husk waste powder, it was concluded that the results of the synthesis process using the coprecipitation method obtained powder which has crystal size about 5 nm. Phase composition contained in durian skin waste nano powder is dominated by phosphate (PO4) elements, namely aluminum phosphate, aluminum silicate hydrate, and titanium nitrate, but evenness of particles still tends to occur agglomeration or clumping caused by oxygen. It can be concluded also that the higher and longer heating treatment the morphology of the durian husk waste particles more evenly and minimize the occurrence of agglomeration.Keywords:  copresipitation method, electrical properties, nanopowder of durian  husk waste, and phase composition